Multimodality imaging of a giant caseous calcification of the mitral annulus - Suzan Hatipoğlu Akpınar; Ruken Bengi Bakal; Ahmet Güler; Nihal Özdemir (KARE Publishing, 2013)
We present an unusual case of giant caseous calcification of the mitral annulus in a 58-year-old female patient. The mass was detected during echocardiography and was defined as a big, round echodense lesion attached to the posterior mitral ring annulus. The patient was further evaluated with a full spectrum of cardiac noninvasive imaging modalities and the diagnosis was confirmed. Caseous calcification of the mitral annulus is a rare entity usually diagnosed by transthoracic echocardiography. Since it is very important to differentiate it from cardiac tumors, complimentary imaging modalities could be used for this purpose if a doubt exists about the diagnosis.